Release of Tissue-Type Plasminogen Activator in Response to Muscarinic Receptor Stimulation in Human Forearm - Jern, Sverker; Selin, Lena; Bergbrant, Anders; Jern, Christina (Thrombosis and Haemostasis, 1994)
We have recently shown that mental stress increases local net release of tissue-type plasminogen activator (t-PA) across the forearm vascular bed. However, the mechanisms responsible for the t-PA release in man during stress are undefined. To study the effects of endothelial cell receptor stimulation and fluid shear stress we used the perfused forearm model to characterize the in vivo tissue plasminogen activator (t-PA) response in man to methacholine (Mch) and sodium nitroprus-side (SNP), at doses calculated to cause similar degrees of vasodilation. The study was performed in 7 healthy young men (age 22-24 yrs) without hypertension, diabetes mellitus, or hypercholesterolemia. Each subject received double-blind step-wise i. a. infusions of Mch (0.1-0.8-4.0 μg/min) and SNP (0.5-2.5-10 μg/min) in randomized order. Each dose step was infused for 5 min. Forearm blood flow was assessed by plethysmography. Net release/uptake was expressed as the product of arterio-venous concentration gradient and forearm plasma flow. At pre-infusion baseline, there was a significant net release of t-PA antigen of approximately 0.9 ng × min−1 × 100 ml−1 and t-PA activity of 3.5 fmol × min−1 × 100 ml−1 across the forearm. I. a. infusion of Mch and SNP increased forearm blood flow from 1.9 to 14.9 and from 1.8 to 12.1 ml × min−1 × 100 mb1, respectively (Mch vs SBP N. S.). Net release of t-PA antigen increased more than 10-fold from 0.9 to 10.7 ng × min−1 × 100 ml−1 after Mch, but fell after SNP (2-way . ANOVA, Mch vs SNP p = 0.05). t-PA activity net release increased from 4.0 to 100 fmol × min−1 × 100 ml−1 after Mch, but switched to a net uptake after SNP (Mch vs SNP p = 0.02). No consistent changes of PAI−1 antigen were observed during either infusion. It is concluded, that endothelial muscarinic receptor stimulation causes a marked increase in net release of t-PA antigen and activity, in conjunction with endothelium-dependent vasodilation. By contrast, increased fluid shear stress per se by receptor-independent vasodilation has little effect on t-PA release.